2022
DOI: 10.3389/fpls.2022.994154
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of the AlkB homologs gene family, PagALKBH9B and PagALKBH10B regulated salt stress response in Populus

Abstract: The AlkB homologs (ALKBH) gene family regulates N6-methyladenosine (m6A) RNA methylation and is involved in plant growth and the abiotic stress response. Poplar is an important model plant for studying perennial woody plants. Poplars typically have a long juvenile period of 7–10 years, requiring long periods of time for studies of flowering or mature wood properties. Consequently, functional studies of the ALKBH genes in Populus species have been limited. Based on AtALKBHs sequence similarity with Arabidopsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 89 publications
1
8
0
Order By: Relevance
“…It highlights the intricate regulatory mechanisms underlying plant growth and adaptation. A previous study reveals that ALKBH10B specifically regulates the floral transition process by demethylating transcripts of key flowering time genes, including flowering locus T (FT) and squamosa promoter binding protein-like 3 (SPL3) in Arabidopsis [ 86 ]. Another study focuses that YTH proteins are involved in various plant processes, including embryogenesis, flowering transition, root development, stem cell fate determination, circadian rhythm, leaf morphology, leaf coat development, nitrate signalling, fruit maturation, gametophyte development, phytohormone responses, and stress responses [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…It highlights the intricate regulatory mechanisms underlying plant growth and adaptation. A previous study reveals that ALKBH10B specifically regulates the floral transition process by demethylating transcripts of key flowering time genes, including flowering locus T (FT) and squamosa promoter binding protein-like 3 (SPL3) in Arabidopsis [ 86 ]. Another study focuses that YTH proteins are involved in various plant processes, including embryogenesis, flowering transition, root development, stem cell fate determination, circadian rhythm, leaf morphology, leaf coat development, nitrate signalling, fruit maturation, gametophyte development, phytohormone responses, and stress responses [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in cotton, GhALKBH10B was found to be downregulated under different abiotic stresses [ 15 ]. Similarly, in Populus , salt treatment induced the expression of PagALKBH10B [ 33 ]. In this study, we observed significant upregulation of SlALKBH10B expression in response to ABA, drought, and salt treatments ( Figure 2 C,G,H).…”
Section: Discussionmentioning
confidence: 99%
“…In cotton, silencing GhALKBH10B led to improved salinity tolerance [ 15 ], and mutation of GhALKBH10B enhanced drought resistance during the seedling stage [ 16 ], indicating a negative regulation of both salt and drought tolerance by GhALKBH10B. Moreover, heterologous expression of PagALKBH10B in Arabidopsis resulted in increased salt tolerance but decreased drought tolerance in transgenic lines [ 33 ], implying a positive regulation of salt tolerance and a negative regulation of drought tolerance by PagALKBH10B. These findings highlight the diverse and even opposing biological functions of ALKBH10B in regulating salt and drought tolerance across different plant species.…”
Section: Discussionmentioning
confidence: 99%
“…m 6 A/A ratio measurement is referenced and refined following our previous research (Zhao, Guo et al, 2022). Total RNA was isolated from the leaves by TRIzol reagent (ET121, TransGenBiotech), and RNA quality was detected by spectrophotometer (Thermo Scientific) and agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%